Free Activation Series Vol. 3 : [Visual Virus] - Fairey, Shepard (Seattle : Art & Revolution Organization, 2000)
Perks ; Reas ; Espo ; Ro Starr ; McMullen, Bill ; Space Invader ; Zevs ; Delta ; Wolfe, Shawn
Visual Virus, Art & Revolution Organization, Seattle, 2000
boek
Keywords: Fairey, Shepard